513 An international survey of practitioners to define the activities required to deliver safe deprescribing and their determinants. (13th April 2023) - Scott, S; Buac, N; Wright, P; Bhattacharya, D
Abstract: Introduction: Despite significant efforts to increase deprescribing (1), marginal progress has been achieved (2). Deprescribing is a complex process involving multiple steps and activities, of which some may be routinely undertaken whilst others require interventions to support behaviour-change. Aim: We aimed to develop an internationally derived specification validated by practitioners from multiple health systems that stipulates both the steps and activities required to deliver those steps of safe deprescribing. We also aimed to estimate the extent to which the required activities are currently undertaken and identify the barriers and enablers that need addressing to deliver safe deprescribing. Methods: We formulated an electronic survey comprising literature reported deprescribing activities. Relevant networks in 25 countries e.g., British Geriatrics Society and Australian deprescribing network, emailed the survey link to all of their member practitioners. Respondents reported the frequency with which they thought each deprescribing activity was undertaken in practice within their peer group on a five-point Likert scale ranging from 1 (never) to 5 (always) and whether it was important. We invited extended responses regarding the barriers and enablers to deprescribing and analysed these using the Theoretical Domains Framework (TDF). Results: From 263 respondents 77.9% were prescribers; 110 (41.8%) were doctors, 85 (32.3%) were pharmacists, 44 (16.7%) were nurses and 24 (9.1%) were other healthcare professionals. Eighteen activities were combined into four deprescribing steps summarised in table 1. All were considered important and clinical activities were 'often' or 'always' undertaken. Patient orientated activities were only 'sometimes' undertaken. The barriers and enablers requiring addressing are in the TDF domains of 'social influence' to support practitioners to undertake patient orientated activities and 'environmental context and resources' to ensure they have sufficient capacity. Conclusion: An internationally derived literature and practice informed process for safe deprescribing has been established. Social desirability bias may have inflated reported frequency of activities being undertaken. We therefore chose reporting on the collective rather than own behaviour, to ameliorate these effects. Organisations should prioritise the inadequate collaboration with patients through addressing practitioners' behavioural determinants. References: 1. Scott S, Clark A, Farrow C, May H, Patel M, Twigg MJ, et al. Deprescribing admission medication at a UK teaching hospital; a report on quantity and nature of activity. International journal of clinical pharmacy. 2018;40(5):991–6. 2. O'Mahony D, Gudmundsson A, Soiza RL, Petrovic M, Cruz-Jentoft AJ, Cherubini A, et al. Prevention of adverse drug reactions in hospitalized older patients with multi-morbidity and polypharmacy: the SENATOR* randomized controlled clinical trial. Age and Ageing. 2020;49(4):605–14.